2007
DOI: 10.1210/me.2007-0042
|View full text |Cite
|
Sign up to set email alerts
|

Synaptosomal-Associated Protein 25 Gene Expression Is Hormonally Regulated during Ovulation and Is Involved in Cytokine/Chemokine Exocytosis from Granulosa Cells

Abstract: During ovulation, granulosa cells and cumulus cells synthesize and secrete a wide variety of factors including members of the IL cytokine family via the process of exocytosis. Exocytosis is controlled by the soluble N-ethylmaleimide-sensitive fusion protein attachment protein receptor complex consisting of proteins residing in the vesicle membrane and the plasma membrane. One of the soluble N-ethylmaleimide-sensitive fusion protein attachment protein receptor proteins, synaptosomal-associated protein (SNAP)25,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 61 publications
3
73
0
Order By: Relevance
“…It is postulated that PR, a ligand-inducible transcription factor, controls ovulation by regulating the expression of a unique network of downstream genes. Consistent with this hypothesis, Richards and coworkers identified three novel genes, a disintegrin and metalloprotease with thromboxan motif 1 (ADAMTS-1) (29), cyclic GMP-dependent protein kinase II (cGKII) (34), and synaptosome-associated protein 25 (Snap25) (32), as potential mediators of PR function in the ovary. Our laboratory has recently reported that endothelin-2 (ET-2), which is induced in the preovulatory follicles in a PR-dependent manner, is a critical regulator of follicular rupture (25).…”
mentioning
confidence: 85%
“…It is postulated that PR, a ligand-inducible transcription factor, controls ovulation by regulating the expression of a unique network of downstream genes. Consistent with this hypothesis, Richards and coworkers identified three novel genes, a disintegrin and metalloprotease with thromboxan motif 1 (ADAMTS-1) (29), cyclic GMP-dependent protein kinase II (cGKII) (34), and synaptosome-associated protein 25 (Snap25) (32), as potential mediators of PR function in the ovary. Our laboratory has recently reported that endothelin-2 (ET-2), which is induced in the preovulatory follicles in a PR-dependent manner, is a critical regulator of follicular rupture (25).…”
mentioning
confidence: 85%
“…These proteins include NSF, ␣ -SNAP, SNARE, SNAP23, syntaxin-5, and VAMP4. Steroidogenic cells express high levels of some members of the SNARE protein family, such as Syntaxin-17, SNAP23, and SNAP25; these are hormonally regulated in ovarian granulosa cells (154)(155)(156)(157)(158). SNARE additional introns present in the MLN64-START domain genomic sequence are also conserved.…”
Section: Transport Of Cholesterol To Mitochondria: Cholesterol-bindinmentioning
confidence: 99%
“…Because the induction of IL-6 is regulated not only by AREG (115) but also by progesterone receptor (PGR) (115,119) and C/EBPβ, both of which are essential for ovulation, it is tempting to speculate that IL-6 may mediate some key process downstream of PGR and C/EBPβ in granulosa cells or cumulus cells. Moreover, the expression of synaptosomal-associated protein 25 (SNAP25), an important component controlling neuronal-like secretion of cytokines from granulosa cells, is also regulated by PGR (120). Thus, the importance of locally produced and secreted ovarian cell-derived cytokines during ovulation needs to be analyzed further, and these cytokines may affect several ovulation-related processes including follicle rupture, COC transport, and fertilization (117).…”
Section: New Insights Into Factors Controlling Ovulation and Luteinizmentioning
confidence: 99%